Is the surge in respiratory syncytial virus related to the COVID-19 pandemic? a clinical-based review - Khabieh, Shelley; Bassoul, Albert; Ftiha, Farage (International Journal of Contemporary Pediatrics, 2021)
Respiratory syncytial virus (RSV) has been around for many years. Symptoms of the virus includes: cough, runny nose, loss of appetite, and a possible ear infection. Often times, the patient presents with bronchiolitis, which eventually escalates to RSV. Children most commonly affected by RSV are between the ages of 0-2. In December 2019, the first case of SARS-CoV-2 was discovered in China. Normally, the RSV virus sparks around the winter months; however, throughout the COVID -19 pandemic, RSV was at its all-time low. When SARS-CoV-2 started to decline in early April 2021, there was a spike in the respiratory syncytial virus among children.